2023
DOI: 10.1080/17482631.2023.2176979
|View full text |Cite
|
Sign up to set email alerts
|

“I can’t remember the last time I was comfortable about being home”: lived experience perspectives on thriving following homelessness

Abstract: Purpose Strategies for preventing and ending homelessness are frequently measured by their effectiveness on indices of tenancy sustainment. To shift this narrative, we conducted research to identify what is needed to “thrive” following homelessness from the perspectives of persons with lived experience in Ontario, Canada. Methods Conducted in the context of a community-based participatory research study aimed at informing the development of intervention strategies, we i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
(76 reference statements)
0
2
0
Order By: Relevance
“…The parent study, called the ‘Transition from Homelessness Study’, involved qualitative interviews with PWLEH and SPOL. Findings detailing the perspectives of PWLEH in this research and our co‐design process can be found in two separate papers (Marshall, Phillips, Holmes, Todd, Hill, Panter, Easton, Jastak, et al, 2022; Marshall, Phillips, Holmes, Todd, Hill, Panter, Easton, Landry, et al, 2022). Methods and findings associated with SPOL interviews conducted across both recruitment sites are detailed in this paper.…”
Section: Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…The parent study, called the ‘Transition from Homelessness Study’, involved qualitative interviews with PWLEH and SPOL. Findings detailing the perspectives of PWLEH in this research and our co‐design process can be found in two separate papers (Marshall, Phillips, Holmes, Todd, Hill, Panter, Easton, Jastak, et al, 2022; Marshall, Phillips, Holmes, Todd, Hill, Panter, Easton, Landry, et al, 2022). Methods and findings associated with SPOL interviews conducted across both recruitment sites are detailed in this paper.…”
Section: Methodsmentioning
confidence: 94%
“…These include high rates of mental illness and substance use disorders (Hossain et al, 2020), traumatic brain injury (Hwang et al, 2008), poverty (Gaetz et al, 2016), housing instability (Macnaughton et al, 2015) and food insecurity (Parpouchi et al, 2016). Although it could be assumed that these needs are alleviated upon obtaining housing, research suggests that PWLEH struggle to thrive following homelessness by continuing to experience difficulties with managing the symptoms of mental illness, substance misuse, poor community integration, a lack of engagement in meaningful activity, unemployment and poverty (Marshall et al, 2017, 2018, 2019, 2021; Marshall, Phillips, Holmes, Todd, Hill, Panter, Easton, Jastak, et al, 2022; Poremski et al, 2015; Stergiopoulos et al, 2014; Tsai et al, 2012; Tsemberis et al, 2004). Leaving these needs unmet has the potential to perpetuate the cycle of homelessness, decrease housing stability and prolong social and health challenges for this population.…”
Section: Introductionmentioning
confidence: 99%